PENGARUH KUALITAS AKTIVA PRODUKTIF TERHADAP RETURN ON ASSETS (STUDI PADA BANK UMUM YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2006-2010 ) - Nazrantika Sunarto; Supriati Supriati (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract:The Effect of Quality of Productive Assets to Return on Assets (a stu- dy in Commercial Banking that Listed on Indonesia Stock Exchange Period2006-2010). This research aims to analyze the effect of the variable KAP to- ward ROA. The samples used were 24 commercial banks listed in the Indo- nesia Stock Exchange in the period 2006-2010 were taken by purposive sam- pling. The analysis technique used is simple linear regression with small qua- dratic equations and test hypotheses using t-statistics for testing the partial re- gression coefficients with a significance level of 5%. Analysis of the test results indicate the magnitude of the effect on ROA is KAP 47%, while 53% is influen- ced by other factors not included in our model. From thet-test results can be concluded, that the Quality of Productive Assets (KAP) has a significant nega- tive impact to Return on Assets. Keywords: Quality of Productive Assets (KAP), Return on Assets (ROA), Commercial Banks, Listed on Indonesia Stock Exchange